Fertilizantes organominerais líquidos como atenuadores da salinidade da água durante a formação de mudas do maracujazeiro-amarelo. - Silva, Katia Gomes da (2021)
After harvesting, papaya has a high respiratory rate and rapid ripening, with loss of green color and tissue softening. This research aimed to evaluate the conservation of papaya papaya at room temperature and minimally processed, using chitosan and gelatin-based coatings. The experiments were carried out at the Postharvest Physiology Laboratory, CCHSA/UFPB. The fruits were selected, washed and sanitized, soon after they were subjected to the following treatments: control (distilled water), 1% chitosan, 4% gelatin, 1% chitosan + 4% gelatin (BLEND) and 1% chitosan under 4% gelatin (layer-under-layer). Then they were naturally dried and stored for 10 days at room temperature of 26±0.3 °C and relative humidity of 67±6%. The FTIR infrared spectroscopy of the coatings, the loss of fresh weight, firmness, skin color (L*, a*, b* and Hue angle), pH, titratable acidity, soluble solids (SS), ascorbic acid, lycopene were evaluated. , β-carotene, phenolic compounds, total sugars, catalase enzyme and macro and micro mineral contents. The second experiment consisted of submitting the minimally processed papayas to the same conditions described above, but stored under refrigeration at 5.0±1 ºC and 80±5% RH. The coatings based on chitosan + gelatin (BLEND), chitosan under gelatin (layer-under-layer) and gelatin, promoted the maintenance of the quality of papaya stored at room temperature for ten days. The coatings were able to reduce mass loss, maintained firmness, the green color of the fruits, had lower SS contents, showing that they also delayed ripening, had lower polyphenol contents, lower variations in acidity and ascorbic acid, maintenance in the levels of lycopene and β-carotene and increased catalase activity throughout the days. The BLEND treatment showed the best results in maintaining fruit quality. Thus, the use of gelatine and chitosan polymers is a viable alternative for preserving papayas at room temperature. Gelatin and chitosan based coatings under layer-by-layer gelatin had a positive effect on the conservation of freshly processed papaya, delaying the maturation of these fruits. The coatings were able to reduce the loss of fresh weight, maintaining the firmness and orange color of the fruit pulp. They presented low SS contents during the conservation period, smaller variations in acidity, influencing ripening. The treatment with gelatin showed low contents of polyphenols. The layer under layer did not show variations in the contents of ascorbic acid. The treatments did not vary in lycopene and β-carotene content over the days, showing small increases in total sugars. Thus, the use of gelatin polymers and the treatment of chitosan under gelatin is a viable alternative for the conservation of minimally processed papayas.